Perbandingan Hasil Analisa Perhitungan Rangka Kuda-Kuda Kayu Dengan Menggunakan SAP-2000 dan Metode Titik Buhul - Sudarno P Tampubolon (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2022)
This research is a study that discusses the comparison of the results of the analysis of the calculation of the forces on the wooden framework using the Structure Analysis Program-2000 (SAP-2000) and method of joint. The value of each force of vertical bars, horizontal bars, tensile bars, and compression members at each point of the wooden framework will be calculated on three wooden framework spans with spans of 7m, 9m, and 11m. Comparison of the results of the calculation of the value of the rod force from the two methods will be compared to see the efficiency of the calculation analysis of the two methods. From the results of the calculation of the method of joint and the Analysis of Structure Analysis Program-2000 (SAP-2000) in calculating and analyzing the value of each vertical bar force, horizontal bar, tension member, and compression member, the difference between each rod force is at (0- 0.51) kg. This shows that the calculation analysis using the Structure Analysis Program-2000 (SAP-2000) is faster and more efficient in calculating each bar force.